The Role Creative Writing in Paragraph Writing Class - Lutfiah, Asti; Ilham, Ilham; Hudri, M.; Aryani, Etika (Scripta : English Department Journal, 2025)
This study employed a systematic literature review design to examine the role of creative writing in enhancing paragraph writing instruction. By analyzing relevant quantitative research published between 2010 and 2025, the study explores how creative writing influences essential aspects of paragraph development, including organization, coherence, clarity, and overall writing competence. Findings indicate that creative writing activities enable students to generate ideas more effectively, refine structural elements, and apply critical thinking in their writing. Beyond technical improvement, creative writing also fosters engagement, motivation, and self-expression, allowing students to overcome challenges such as writer’s block and to write with greater fluency and confidence. Importantly, the review reveals that creative writing not only strengthens linguistic accuracy but also cultivates creativity, which is vital for producing meaningful and impactful compositions. These outcomes highlight the dual cognitive and emotional benefits of integrating creative writing into the curriculum. The implications emphasize the need for educators to adopt creative strategies that balance skill development with imaginative exploration, thereby offering a holistic approach to improving writing instruction in educational settings.